Evaluation of Reverse Logistics Management Performance In After-Sales Repair-Return Service - Mohammad Alfian; Nofrisel, Nofrisel; Setyawati, Aswanti (Dinasti International Journal of Digital Business Management, 2024)
The purpose of this research is to evaluate the performance of reverse logistics management in terms of after sales service repair return activities such as the activity of managing the broken item, export and import, and broken item handling activities at the warehouse etc. using the purposive sampling, the respondents selected consists of 5 person whose active engage in the activity. This research is conducted through descriptive qualitative data analysis with interviews, observations, and internal documentation. According to the research results of reverse logistics management on repair returns, there are still a lot of rooms needed to improve the performance, and speed up the lead time. There is still a room for improvement needed such as SOP standardization of each reverse logistics activities involved itself, should have need some of goods movement configuration and management such as, flow of communication, flow of goods, flow of documents and the administrative work improvement on creating the export import license permit document to avoid the error which can lead to a longer lead time.